Pemikiran Balaghah Menurut Ibn Qutaibah: الفكر البلاغي عند قتيبة - Alif Alvian Mawaddi Hamid; Ahmad Dardiri; Raswan; Achmad Fudhaili (Indo Publishing, 2025)
Balaghah is the science that studies the beauty and effectiveness of language in conveying meaning accurately and beautifully. Ibn Qutaibah (d. 276 AH) is one of the early figures who paid great attention to the aspect of balaghah in the study of language and interpretation. Through his works such as Ta’wil Mushkil al-Qur’an and Adab al-Katib, he proposed an approach that balances between literal meaning and contextual meaning, while emphasizing the importance of aesthetic and rhetorical elements in understanding texts, particularly the Qur’an. This research shows that Ibn Qutaibah's rhetorical thought (balaghah) focuses on the understanding of the Arabic language and its rhetorical styles. It provides an in-depth analysis of poetry and prose, covering concepts such as majaz, kiasan, isti’arah, tasybih, tasjim, and emphasizes the importance of meaning and style in expression, contributing to the development of rhetorical studies. This method employs library research, which is a data collection method that involves understanding and studying theories from literature related to the research. The data sources for this research are obtained from relevant literature such as books, scientific articles, or journals on the chosen topic. The results of this study indicate that Ibn Qutaibah's balaghah thought emphasizes and focuses on the understanding of the Arabic language, the depth of meaning, and the accuracy in conveying messages.